Legal Protection of Consumers in the Implementation of Illegal Parking in Connection with the Consumer Protection Law (Case Study of Vehicle Parking in City Park) - Fathanudien, Anthon; Fauziah, Siti (Veteran Law Review, 2025)
The behavior and life of the community is always dynamic in accordance with the needs of life as a means of support in carrying out daily activities. Because public service factors related to public transportation are not clear about the route and route, the majority of people prefer to use private vehicles, this situation is in line with the intensity of vehicle sales. Motorized vehicle parking lots are a necessity for vehicle owners, therefore parking must receive serious attention, especially regarding its regulation. As in the Kuningan Regency City Park area, the community always needs a safe and orderly parking lot, but there are some people who do not understand and are irresponsible in terms of utilizing parking management such as illegal parking fees. One of the important things in parking management is the issue of protection for consumers of parking service users regarding the payment of parking rates that exceed normal rates and are carried out by illegal parking attendants and are included in illegal parking fees. The purpose of this research is to find out legal actions based on regulations on Consumer Protection for individuals who collect illegal parking fees in Kuningan Regency and the role of the Parking Related Service in Kuningan Regency, namely the Parking Section of the Kuningan Regency Transportation Office.This research is an empirical legal research using field research and also through literature data and interviews as data collection methods. The interview was conducted to one of the resource persons who has authority in the parking lot. The results of this study indicate that parking attendants should be able to pay attention to consumers as stipulated in the regulations on Consumer Protection and parking attendants who have been equipped with Special Parking Uniforms and Task Orders (SPT) collect parking fees in the field and then given and supervised by the supervisor, after being given to the supervisor, the supervisor gives it to the manager to be deposited into the Local Government treasury once a week. Efforts made in curbing illegal levies on parking services are conducting raids/patrols, directly reprimanding and inviting official parking attendants.